Delik Culpa dalam Berkendara (Studi Kasus Tindak Pidana Pelanggaran Lalu Lintas di Kabupaten Gorontalo) - Tobing, Vania Athalia Lumban; Permatasari, Angelina Dewi; Immanuel A.S, Laurentius; Rajagukguk, Elisabeth; Tarina, Dwi Desi Yayi (Media Hukum Indonesia (MHI), 2024)
The crime of culpa in driving is a violation of general criminal law because of negligence from the driver side, where accidents that result in fatalities might have occurred. Drivers who breach the traffic law and allow the death of a person by their negligence may be prosecuted based on the prevailing laws. This research is specifically conducted as a case study of traffic law violation in Gorontalo Regency due to driver negligence. That is all because of negligence due to a lack of awareness of safety on the road. From this very issue, the author conducted research on the application of culpa in driving, based on a case study of traffic violations in Gorontalo Regency which led to a prosecution in conformity with legal policies in force. Methods The method used in this research is a literature review by referring to various literature sources, either in the form of books, journals, papers, news, and others. The results of this study indicate that accidents occur due to a lack of awareness from the driver, which leads to negligence, or culpa in Latin, causing death. This research also underlines the importance of driver responsibility while driving. The fatal incidents teach a lesson of traffic safety and implementation of the law as per the legal policies against the traffic violators, which works like education for the general public in order to drive carefully to attain traffic safety.